Cellular electrophysiologic properties of old canine atria provide a substrate for arrhythmogenesis - Anyukhovsky, E (Cardiovascular research, 2002)
The incidence of atrial fibrillation increases with age. We hypothesized that aging-associated changes in the atrial action potential (AP) and conduction velocity provide a substrate for abnormal conduction and arrhythmogenesis. We used microelectrode techniques to record AP from the endocardium of the right atrial wall of dogs aged 1-5 (adult) and >8 years (old). Conduction velocity was measured between two microelectrodes 3-10 mm apart. Histological study was carried out to assess fibrosis. Whereas resting potential, AP amplitude and V(max) did not differ with age, the plateau was more negative and AP duration was longer in old tissue. The L-type calcium current (I(Ca,L)) agonist Bay K8644 (10(-8)-10(-6) mol/l) elevated the plateau and shortened APD more in old than in adult, such that AP contour in old atria approached that of adult. In contrast, the I(Ca,L) blocker nisoldipine (10(-8)-10(-5) mol/l) depressed the plateau in adult and had no effect in old. There was no difference between the two groups in conduction velocity of normal beats, whereas for early premature impulses, reduced conduction velocity and a wider time window manifesting slow conduction were detected in old in comparison to adult tissue. A twofold increase in the amount of fibrous tissue was detected in old atria. Our data show significant differences in contour of AP in adult and old atria. The responses to Bay K8644 and nisoldipine suggest a decreased I(Ca,L) in old atrial tissue. The alterations in AP contour and increased fibrosis may be responsible for slower conduction of early premature beats in old atria. The age-related changes in conduction of premature beats are consistent with those observed in patients with paroxysmal atrial fibrillation and may contribute to the greater propensity to atrial fibrillation in the aged.